Memerangi Disinformasi : Melanjutkan Pembangunan Perdamaian Illiberal di Indonesia - Ubaidillah Ubaidillah (Jurnal Masyarakat dan Budaya, 2022)
This article discusses the construction of the kerata basa discourse and the meaning of cultural teachings from the discourse with an anthropological linguistic approach. Data on the kerata basa discourse was collected from observations and interviews in the Cirebon Regency area as well as literature studies. The construction of the kerata basa discourse is formed with the constituent words and utterances. The constituents of words and utterances share portions to explain each other; half of the discourse meaning is in the word constituents for referential meanings, and half is in the utterance constituents to describe referential meanings in Javanese culture. The two constituents are dialectically related in forming a system of meaning. The meaning of the teachings contained in the kerata basa discourse implies the responsibility of further interpretation to the recipient. The arbitrary nature of the kerata basa has a grip both in terms of construction and meaning that makes its construction results acceptable to fellow Javanese people. The kerata basa is a Javanese cultural grammar; a grammar at the parole level that produces connotative meanings and is not a langue.